The darkest path - Hirsch, Jeff (Scholastic Press, 2013)
Since he was captured by the Glorious Path, a militant religion based on the teachings of a former soldier, fifteen-year-old Cal has served the Path in its brutal war with the remains of the United States government, and tried to survive and protect his younger brother, but when he kills an officer to protect a stray dog, Cal is forced take his brother and the dog and run.